The Fox and The Dog LEVEL 2 - Mitchell ,H.Q (MM PUBLICATIONS (E. MOUTSOU & CO O.E.), 2005)
One day, a hungry little fox is walking in the forest... Read along and find out what adventure she gets herself into and how a true friend will try to help her. A classic story with a moral - and a lot of fun, too!